2015
DOI: 10.1186/s40249-015-0056-y
|View full text |Cite
|
Sign up to set email alerts
|

When are patients lost to follow-up in pre-antiretroviral therapy care? a retrospective assessment of patients in an Ethiopian rural hospital

Abstract: BackgroundThere is concern about the increasing rates of loss to follow-up (LTFU) among pre-antiretroviral therapy (pre-ART) patients in Ethiopia. Little information is available regarding the time when pre-ART patients are lost to follow-up in the country. This study assessed the time when LTFU occurs as well as the associated factors among adults enrolled in pre-ART care in an Ethiopian rural hospital.MethodsData of all adult pre-ART patients enrolled at the Sheka Zonal Hospital between 2010 and 2013 were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…In Myanmar, within the IHC programme, an alarmingly high attrition rate was observed with nearly 70% being either dead or LTFU at the end of 4 years. This is one of the highest rates of attrition ever reported, in line with published reports from Asia and Africa ( 6 8 , 15 21 ). Most of the attrition occurred in the early stages of enrolment into care: 90% of attrition occurred within first 6 months with nearly half in the first month.…”
Section: Discussionsupporting
confidence: 88%
“…In Myanmar, within the IHC programme, an alarmingly high attrition rate was observed with nearly 70% being either dead or LTFU at the end of 4 years. This is one of the highest rates of attrition ever reported, in line with published reports from Asia and Africa ( 6 8 , 15 21 ). Most of the attrition occurred in the early stages of enrolment into care: 90% of attrition occurred within first 6 months with nearly half in the first month.…”
Section: Discussionsupporting
confidence: 88%
“…These included TB [39,[44][45][46] and diarrhea for more than 3 months led a risk of death [18]. Nine papers reported that provision of isoniazid preventive therapy (IPT) [17,18,35,38,39,50,54] and CPT [25,29] prophylaxis indicted that optimize patient retention.…”
Section: Clinical Related Factorsmentioning
confidence: 99%
“…Among structural factors, barriers to health care delivery, such as distance to a health care facility, have been commonly reported [8,15, 16].Psychosocial circumstances, including the presence of social support and an ability to disclose one's HIV status, have been found to affect linkage to care and ART initiation [17, 18]. In addition, behavioural patterns related to perceptions of the health bene ts of early ART [19][20][21][22], as well as an acceptance of HIV positive status, have been strongly linked to the level of the patients' engagement in care and ART initiation [10,19,23]. Sociodemographic characteristics, such as patient age and gender, have also been frequently reported to be associated with late linkage to care and delays in ART initiation [17,20,[24][25][26][27].Across published studies, there are variations in de nitions of HIV care-related health outcomes as well as contextual differences associated with the risk factors for late linkage to care and delayed ART initiation.…”
mentioning
confidence: 99%